PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA AUGMANTED REALITY (AR) TERHADAP KEMAMPUAN ANALISIS MATERI PECAHAN MATA PELAJARAN MATEMATIKA SISWA KELAS V GUGUS VI KECAMATAN SAWAN - Kadek Ningsih; I Nyoman Pancaria; L. Heny Nirmayani (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to determine the significant differences in the analytical abilities of students taught using the Problem-Based Learning (PBL) model assisted by Augmented Reality (AR) media and those taught without the PBL model assisted by AR media on fraction material in mathematics subjects for fifth-grade students in Cluster VI, Sawan District. This research employed a quasi-experimental design using a post-test only control group design. The population consisted of 172 elementary school students in Cluster VI, Sawan District, and 82 students were selected as the sample. Data were collected through observations, interviews, tests, and documentation to obtain information regarding students’ analytical abilities in fraction material in mathematics learning. The results showed that the average analytical ability score of the experimental class was 78.50, while the control class achieved an average score of 70.00. Therefore, the implementation of the PBL model assisted by AR media had a positive effect on students’ analytical abilities in fraction material in mathematics subjects for fifth-grade students in Cluster VI, Sawan District.